Luis Javier Ortiz Mesa, Obispos, clérigos y fieles en pie de guerra. Antioquia, 1870-1880 (Medellín: Editorial Universidad de Antioquia, Universidad Nacional de Colombia, Sede Medellín, 2010), 456 p. (2012)
COL0015669